Parasites affect hemocyte functionality in the hemolymph of the invasive Atlantic blue crab Callinectes sapidus from a coastal habitat of the Salento Peninsula (SE Italy) - PAGLIARA, PATRIZIA; MANCINELLI, GIORGIO (Mediterranean Marine Science, 2018)
The blue crab Callinectes sapidus is an invasive alien species in the Mediterranean Sea. In native habitats, it is subjected to mortalities determined by different pathogens, including the dinoflagellate Hematodinium perezi, a parasite also affecting other brachyuran species. Specifically, Hematodinium-associated disease is acknowledged worldwide as an emerging infection for commercially important crustacean species, but the general diffusion in wild species is unknown. Here, a preliminary screening in C. sapidus hemolymph as well as in three indigenous crabs captured in SE Italy, evidenced the presence of unidentified protozoans in more than 70% of specimen, but the number of suspected Hematodinium cells was very low. The parasites occurrence affected C. sapidus hemocytes functionality, interfering with their role in innate immunity (i.e. phagocytosis or DOPA production). More studies are necessary in order to verify the impact of this alien brachyuran on invaded ecosystems as mediated by the spread of parasites and other pathogens.